2009
DOI: 10.1680/macr.2007.00123
|View full text |Cite
|
Sign up to set email alerts
|

A numerical algorithm for the ITZ area fraction in concrete with elliptical aggregate particles

Abstract: In view of the importance of the interfacial transition zone (ITZ) to the macro-properties of concrete, it is essential to determine the ITZ area fraction in concrete. Once the ITZ area fraction is known, the physicomechanical properties of concrete can be predicted based on the three-phase composite model. The intention of the present paper is to develop a numerical algorithm for the ITZ area fraction in concrete with elliptical aggregate particles. By introducing a contact function for two ellipses, the elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
1
13
2
Order By: Relevance
“…9(d). Apparently, the stability of the overlapping detection algorithm is fine and the packing fraction realized by the current model is higher than that (0.60) by Zheng et al [24].…”
Section: D Models For Random Sequential Packing Of Elliptical Particcontrasting
confidence: 60%
See 1 more Smart Citation
“…9(d). Apparently, the stability of the overlapping detection algorithm is fine and the packing fraction realized by the current model is higher than that (0.60) by Zheng et al [24].…”
Section: D Models For Random Sequential Packing Of Elliptical Particcontrasting
confidence: 60%
“…Recently, employing the Perram contact function [21] to check elliptical aggregates overlapping, Zheng et al [24] also simulated the random sequential packing of elliptical aggregates with periodic boundary conditions, and revealed that the maximal random packing fraction reached 0.60 for polydispersed ellipses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if ellipses slightly deviate from circles, the wattle effect will disappear at once [13] . Due to the maximal packing fraction of random packing is higher than that of 0.55 in Bezrukov et al [8] and that of 0.60 in Zheng et al [9] , this 2D elliptical model of random packing is very efficient. In addition, the result of the simulation for random packing of ellipse particles with increasing aspect ratios is that the packing fraction firstly increases and then drops down with increasing aspect ratio.…”
Section: Application Of Modelmentioning
confidence: 93%
“…For example, Bezrukov et al [8] applied a force-biased algorithm for the simulation of a broad spectrum of dense random packing of spheroids and the maximum packing fraction was 0.55. Zheng et al [9] employed Perram contact function [10] to simulate random packing of 2D ellipses in the periodic boundary condition and the maximum packing fraction reached 0.60.…”
Section: Introductionmentioning
confidence: 99%
“…This theory was also applied by Garboczi and Bentz [5] and Du et al [11]. Moreover, Zheng et al [30] adopted the Monte Carlo method to evaluate the ITZ area fractions. Herein the present study, it is assumed that the ITZ layers of aggregate particles are independent of each other, namely, they do not overlap just as that Fig.…”
Section: Evaluation Of the Apparent Diffusion Coefficient D Eff Of Comentioning
confidence: 99%